Edna’s “Moments of Being” and “Wild Zone” of Female Sexuality: A Gynocritical Study of Kate Chopin’s The Awakening - Ferdoush, Jannatul (EAST WEST JOURNAL OF HUMANITIES, 2018)
This paper studies Kate Chopin’s reinterpretation of female sexuality and personal autonomy in The Awakening through the lens of Elaine Showalter’s Gynocriticism. It argues that Edna’s struggle with the traditional idea of female sexual abstention, self-sacrifice, and silence symbolizes her insatiable desire to redefine female identity. The articulation of her overt sexuality in the novella offers a new gateway of understanding a ‘female self ’. Edna’s physical autonomy awakens her to a subversive, compelling, dynamic and liberating “wild” female self within. Edna in her journey into the untamed zone of sexuality through “moments of being” catches a glimpse of the forbidden trajectory of self-knowledge. She yearns to reach her selfhood through these utterly individual moments of awareness, intense power, beauty and personal significance. The unfolding of her female interiority reveals a strong connection between wildness of female eros and creativity. Chopin identifies this so called evil, unrestraint sexuality as an elixir of woman empowerment. Edna’s wandering into her sexual wilderness embodies a new female archetype who writes her own story of resistance and power through her body. Edna’s gradual alienation from androcentric idea of chastity, marriage, motherhood, her celebration of female body, and the final rejection of ‘happy-ever-after reality’ evoke a volcanic eruption of a new femininity in the female literary tradition.